Comparative study of clinical profile and presumptive stressful life events in patients of psychogenic non epileptic seizure and epileptic seizure: a cross sectional study - Rizvi, Abid; Gaur, Rakesh K.; Reyazuddin, Mohammed; Usmani, Mohammed A. (International Journal of Research in Medical Sciences, 2017)
Background:Psychogenic Non Epileptic Seizure (PNES) is one of the most common conditions to be mistaken for epilepsy. No clinical feature is pathognomic of PNES, but some help in distinguishing it from epileptic seizure. Role of psychologically stressful events has been considered central to the pathogenesis of PNES and used in differentiating it from epileptic seizure. The purpose of present study was to compare the clinical profile and number of stressful life events in the two patient groups in Indian population. Methods:50 new patients of epileptic seizure and PNES each, aged 16 to 60 visiting the psychiatric and neurology OPD were selected. Detailed history and physical examination was carried out to exclude any medical illness. Diagnosis was made based on clinical history given by an eye witness and EEG recording. Brain imaging (CT/MRI) was conducted, to rule out any secondary causes of seizure. General health questionnaire 12, and presumptive stressful life event scale was applied on all patients. SPSS 19 was used for data analysis. Chi square was used for categorical data and Man Whitney U test for continuous data. Results:There were significantly more females in the PNES group (P = 0.001) and significantly more illiterate (P = 0.004) .There were no significant difference with regard to the age of onset, marital status. Also there was no statistically significant difference between the two group with regard to number of stressful life event (P = 0.330). Conclusion:Stressful life event should not bias a clinician towards making a diagnosis of PNES.